2014
DOI: 10.5194/acp-14-3623-2014
|View full text |Cite
|
Sign up to set email alerts
|

Regional modeling of tropospheric NO<sub>2</sub> vertical column density over East Asia during the period 2000–2010: comparison with multisatellite observations

Abstract: Abstract. Satellite observations of the tropospheric NO 2 vertical column density (VCD) are closely correlated to, and thus can be used to estimate, surface NO x emissions. In this study, the NO 2 VCD simulated by a regional chemical transport model with emissions data from the updated Regional Emission inventory in ASia (REAS) version 2.1 were validated through comparison with multisatellite observations during the period 2000-2010. Rapid growth in NO 2 VCD (∼ 11 % year −1 ) driven by the expansion of anthrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 34 publications
(44 reference statements)
3
68
0
Order By: Relevance
“…This is likely valid, because satellite NO 2 observations are closely correlated to surface NOx emissions due to the short lifetime of NOx in the troposphere. Anthropogenic NOx emissions and the tropospheric NO 2 VCD simulated by an air quality model for the CEC region, where the anthropogenic NOx emission was the dominant source of NOx, were strongly correlated, with a R 2 higher than 0.9 (Itahashi et al 2014). The annual population data used here were taken from United Nations (2015).…”
Section: Trend Analysesmentioning
confidence: 99%
“…This is likely valid, because satellite NO 2 observations are closely correlated to surface NOx emissions due to the short lifetime of NOx in the troposphere. Anthropogenic NOx emissions and the tropospheric NO 2 VCD simulated by an air quality model for the CEC region, where the anthropogenic NOx emission was the dominant source of NOx, were strongly correlated, with a R 2 higher than 0.9 (Itahashi et al 2014). The annual population data used here were taken from United Nations (2015).…”
Section: Trend Analysesmentioning
confidence: 99%
“…Recently, satellite observations have been widely used as a proxy for emissions data. The NO 2 column has been used to capture NO x emissions (e.g., Miyazaki et al, 2012;Mijling et al, 2013;Itahashi et al, 2014b;Han et al, 2015;Irie et al, 2016), and the SO 2 column has been used for SO 2 emissions (e.g., Lee et al, 2011;Li et al, 2010) and/or volcanic eruptions (e.g., Brenot et al, 2014). Several studies have indicated the importance of different technologies to control emissions (e.g., Li et al, 2010;Wang et al, 2015;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Satellite Observationsmentioning
confidence: 99%
“…In our previous studies (Itahashi et al, 2014a(Itahashi et al, , 2015, which considered data obtained in 2000-2011, emissions from China exhibited a transition from a continuously increasing trend. NO x emissions in China have been rising steadily (Kurokawa et al, 2013;Itahashi et al, 2014b), whereas SO 2 emissions in China peaked in [2005][2006] and subsequently declined due to the introduction of flue-gas desulfurization systems in China's 11th Five-Year Plan (2006 (Kurokawa et al, 2013;Itahashi et al, 2012). Recently, it has been reported that NO x emissions in China declined after 2011-2012 (Irie et al, 2016;Xia et al, 2016;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, satellite observations have been widely used as a proxy for emissions data. NO 2 column have been used to capture NOx emissions (e.g., Miyazaki et al, 2012;Mijling et al, 2013;Itahashi et al, 2014b;Han et al, 2015;Irie et al, 2016) and SO 2 25 column for SO 2 emissions (e.g., Lee et al, 2011;Li et al, 2010) and/or volcanic eruptions (e.g., Brenot et al, 2014). Several studies have indicated the importance of different technologies to control emissions (e.g., Li et al, 2010;Wang et al, 2015;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Satellite Observations 20mentioning
confidence: 99%
“…In our previous studies (Itahashi et al, 2014a(Itahashi et al, , 2015, which considered data for 2000-2011, emission from China was shown to transition from a trend of continuous increase. NOx emission in China has been rising steadily (Kurokawa et al, 2013;Itahashi et al, 2014b), whereas SO 2 emission in China peaked in [2005][2006] and subsequently declined due to the introduction of flue-gas desulfurization systems in China's 11th Five-Year Plan (2006 (Kurokawa et al, 2013;5 Itahashi et al, 2012a). Recently, it has been reported that NOx emission in China declined after 2011(Irie et al, 2016Xia et al, 2016;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Introductionmentioning
confidence: 99%